Organização e representação do conhecimento : fundamentos teórico-metodológicos na busca e recuperação da informação em ambientes virtuais - Miranda, Marcos Luiz Cavalcanti de (2005)
The present work approaches information retrieval in virtual environments analysing search engines performance using natural language in the context of knowledge organization. The research has as starting point theories and methodologies of the knowledge organization for information retrieval found in Library and Information Sciences and Documentation areas. Different forms and levels of information retrieval in the Web were characterized by analyzing search engines available. The search engines were also analyzed in order to identify their potential performance in information retrieval, and in order to verify the information retrieval rate in the Web using natural language. The analyses performed on the given search engines (Altavista, Google and Yahoo) considered as variables documents, terms, occurrences, subject scope and ranking. The results obtained, interpreted on the basis of theoretical and methodological approaches to knowledge organization for Information retrieval in current environments, revealed that this is a valuable support to subsidize knowledge organization in virtual environment. The results also indicate that information retrieval rate may be improved if knowledge organization for Information retrieval in the web considers information processing, mainly based on conceptual relations, approaching human cognitive structures